GENDER DALAM PERSPEKTIF PENDIDIKAN ISLAM - Saniasa; Junaidi; Ondeng, Syarifuddin (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study examines the concept of gender in Islamic education perspectives, focusing on equal educational rights between men and women. Islamic education theologically teaches gender equality based on the Qur'an and Hadith, yet its implementation faces significant challenges due to patriarchal cultural influences and gender-biased interpretations. The research employs a literature review method with a descriptive-analytical approach. Findings reveal that although Islamic teachings emphasize equal educational rights for all individuals regardless of gender, practices are often hindered by conservative social and cultural norms that limit women's educational access. Major challenges include patriarchal interpretations of religious texts, limited educational access particularly in rural areas, and insufficient awareness of gender equality in curricula. Required efforts include inclusive curriculum reform, gender equality-based teacher training, improved educational access for women, and removal of cultural barriers. This study concludes that Islamic education must systematically integrate gender equality principles to realize a fair, inclusive educational system aligned with fundamental Islamic values.